Can Motion Graphic Animation About Snakes Improve Preschoolers’ Detection on Snakes? A Study of Inattentional Blindness - Fang, Jie; Hu, Jiangbo; Wang, Fen; Yan, Congcong; Zhang, Hui (Frontiers in Psychology, 2021)
This study created a motion graphic (MG) animation about the danger of snakes within a story telling structure, which is different from a traditional science animation that relies on explanatory language to explain the scientific concept. The effects of the two types of animations on children’s attentional perception on snakes were compared by an Inattentional Blindness (IB) task. Three groups of children undertook the IB task with one control group who did not watch the animation and the other two groups who watched the MG and the traditional styled animation respectively in advance. The results showed that: (1) Children who watched the animation were significantly more likely to detect the unexpected snake images in the IB task than those who did not watch the animation; (2) Children who watched the MG animation showed a higher detection rate on the snake images than those who watched the traditional animation. The findings indicate that the intervention of animation would increase children’s attentional perception on the key concepts significantly. The MG animation has more impact than the traditional animation on children’s attentional perception on the key information. This study demonstrates that MG animation may have a significant value in promoting science education for young children that merits further explorations in depth.